Unlocking Critical Thinking in Learners: RQA and Concept Maps Working Together - Andi Andariana; Rezeki Amaliah; Depi Triana (Postgraduate, University of Mataram, 2025)
Critical thinking plays a vital role in the learning process, as it supports knowledge development and involves evaluating topics, content, and challenges. This research sought to assess the impact of Reading, Questioning, Answering (RQA)-Integrated Concept Maps (RQA-Integrated CM) on improving students' critical thinking abilities. Using a quasi-experimental with a purpose sampling pretest-posttest one group design, 30 biology students from Patompo University in Makassar, South Sulawesi, Indonesia were sampled for the study. The data were collected through essay tests focused on Human Anatomy and Physiology, designed around critical thinking criteria such as basic clarification, bases for a decision, inference, advanced clarification, supposition and integration, strategies and tactics. The tests consisted of 12 valid and reliable questions. The data were analyzed using Wilcoxon test at a 5% significance level. The findings demonstrated that RQA-Integrated CM positively influenced students' critical thinking. Based on these results, it is recommended that educators utilize RQA-Integrated CM to enhance critical thinking in the classroom